Roosevelt's Populism: The Kansas Oil War of 1905 and the Making of Corporate Capitalism. (January 2020) - Williams, Kyle
Abstract: The map of the American petroleum industry shifted rapidly from the Northeast to the Southwest at the turn of the twentieth century when spectacular gushers were struck first in Texas and soon in California, Kansas, and Oklahoma. The flood of small and mid-size oil producers broke the hold that the Standard Oil Company had for decades held on the industry. Competition defeated monopoly. Or so the conventional story goes. This article offers a more complicated narrative by focusing on conflicts between Standard Oil and independent producers in the booming towns of southeast Kansas in 1904 and 1905. In those years, John D. Rockefeller's firm established a monopoly through technologies of distribution and distillation and the production of scientific knowledge and opaque classifications of commodities. Oil producers revolted. A reform movement turned to the rhetoric and policy ideas of Populism as it sought to use state power to challenge the stranglehold of the "octopus." This article explores the previously unrecognized significance of this movement by showing how the Kansas oil war contributed to the breakup of Standard Oil by the Supreme Court in 1911 and constituted one of the bottom-up sources for the reconstruction of American capitalism.